Doug Morrison and Royce Morrison interviewed by Rob Willis in the Rob and Olya Willis folklore collection - Morrison, Doug, 1934-; Watson, John.; Willis, Rob, 1944-; Morrison, Royce, 1938- (2002)
Folkloric recording. Doug Morrison and his wife Royce talk about saw milling in the Coolah area of NSW; their lives and the changing face of the timber industry in relation to mill owners; environmental and government issues.They are now both retired.
Tape 2: Recitation: local poem (unidentified) -- local poem (unidentified)
Recorded with John Watson.
Recorded on July 4, 2002 at Coolah, N.S.W.
Also available online
Timed summary (3 p.)
Keywords: Morrison, Royce, -- 1938- -- Interviews; Morrison, Doug, -- 1934- -- Interviews; Sawmill workers -- New South Wales -- Coolah -- Interviews; Logging -- Government policy -- Australia; Sawmillers